PENINGKATAN PEMBERDAYAAN MASYARAKAT PESANTREN TRADISIONAL MELALUI PENGEMBANGAN EKONOMI LOKAL DI KOTA SERANG - Sutjipto, Hady; Fadhullah, Fadhullah; Suhendar, Suhendar (Jurnal Pengabdian Dinamika, 2016)
Economic empowerment of Pesantren Traditional, is one of the activities that can improve the ability of students to apply knowledge according to their expertise. KKN PPM provides the opportunity for students to mingle in order to empower and contribute to the settlement of the existing problems in Pesantren Traditional.Achievement of objectives and targets. KKN PPM will be implemented in 3 Pesantren Traditional in District Kasemen in Serang City Banten Province, namely: 1) Increase the ability of students in the application of science and technology in accordance with science and expertise of each 2) Apply the patterns Local Economic Development students to provide knowledge, technology, and economic empowerment in the form of entrepreneurship training for the students and the preachers / cleric in boarding tradisional.3) Empower local potential in creating domestic product, home industry thereby building an independent entrepreneur sustainability. Method of Local Economic Development (LED) to KKN-PPM will provide the opportunity for participating students to work together to mingle directly with the public schools. Collaborating with partners, DPL, this activity begins with providing a briefing to the participants KKN-PPM then provide counseling, training, and application of appropriate technology and mentoring to further develop the products of traditional pesantren community. This method is expected to increase the potential and create sustainable independent entrepreneurs.